Implementation of Depomedroxy Progesterone Acetate and Cyclofem Injective Contraception Devices in Family Planning Acceptors in Bantimurung Health Center, Maros District - Wijayanti, Lumastari Ajeng; Sari, Erma Puspita; Handayani, Sri; Mildaratu, Mildaratu; Ula, Zumrotul; Sari, Rini Gustina (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
High interest in the contraceptive Medroxy Progesterone Acetate goes hand in hand with acceptor complaints about weight gain. This study aims to determine the effect of parity on the continued use of Medroxy Progesterone Acetate and Cyclofem injections. This research was carried out at the Bantimurung Maros Community Health Center with the research design used was a Cross Sectional Study research. In this research design, a survival analysis study will be used. Data analysis was carried out univariately, bivariately using the logrank test, and multivariately using the Cox Proportional Hazards Model Regression test. The results showed that parity was a factor related to continued use, with a value of (p = 0.011). Our hope is that the community, especially mothers who want to become acceptors, will be more effective in using and becoming acceptors of injectable family planning.